PENGEMBANGAN POTENSI LITERASI EKOWISATA DESA NGADAS MELALUI EDUKASI DWIBAHASA - Prasetyaningrum, Dian Islami; Wahyuningtyas, Agustina Shinta Hartati; Kusuma, Putra Gylang Rachmad; Ashif, Faiz Salas; Pramesti, Amelia Putri; Setiawan, Nisrina Marlita (Yayasan Education and Social Center, 2025)
Developing ecotourism literacy in Ngadas Village is an effort to increase community understanding of the importance of environmental conservation and sustainable use of natural potential. This article highlights a community service initiative that focuses on community empowerment through bilingual education to introduce the concept of ecotourism. This program aims to improve communication skills in Indonesian and English among village residents, especially in the context of ecotourism, to broaden the horizons of village communities, especially school-age children at the elementary school (SD) level. Bilingual educational activities include an introduction to the natural and industrial ecotourism potential in Ngadas Village, training and learning about language in English vocabulary and simple conversations with foreign tourists. In its implementation, this community service activity received a warm welcome from the participants. It was reflected in the participants' activeness during the activity. The expected result is the creation of a community better prepared to face the development of the local ecotourism sector that is globally competitive and able to contribute to nature conservation and improve the local economy. Hopefully, this program can become an effective community empowerment model for other tourist villages in Indonesia